EFISIENSI USAHATANI BUDIDAYA KOLAM AIR TAWAR DI KECAMATAN BAJENG KABUPATEN GOWA - Naidah, Naidah (Jurnal Ekonomi Balance, 2011)
This study aims to determine the efficiency of freshwater fish farming in Gowa District so that it can be estimated the economic feasibility of freshwater ponds. Research using primary and secondary data, data analysis is done through calculation of R / C ratio. The results showed that the freshwater pond cultivation conducted by the community of Bajeng District of Gowa Regency is profitable and feasible to be cultivated. This is shown from the R / C ratio of 13.61 which means that the farming is at a favorable level. The income received is generally moderate, indicated by the number of respondents who have income between Rp. 39,145,000 - 149,793,750 as many as 80% of respondents.